Bioresorbable Vascular Scaffolds in a Real‐World Patient Population‐Results From a Mid‐Term Angiographic Follow‐Up. (21st June 2016) - Saad, Mohammed; Abdin, Amr; Thiele, Holger; Desch, Steffen; Ibrahimi, Pranvera; Wikstroem, Gerhard; Hoeher, Martin; Henein, Michael
Abstract : Aim: We aimed to investigate the safety and efficacy of bioresorbable vascular scaffolds (BVS) in daily use in a real‐world patient population. Methods and Results: Between March 2013 and September 2014, 224 patients (233 lesions) were treated with BVS at a tertiary care center. Patients underwent follow‐up coronary angiography 3–6 months after implantation. Clinical presentations were stable angina in 101 patients (45.1%), unstable angina in 47 (21.0%), NSTEMI in 38 (17.0%), and STEMI in 38 (17.0%) patients. Twenty‐two patients (27 lesions) had chronic total occlusion (CTO). Procedural success was achieved in all patients. Two patients died in the follow‐up period due to BVS thrombosis (0.9%). In‐hospital death occurred in further 3 patients (1.3%) due to other causes not related to the BVS implantation. Total BVS thrombosis was 3.1% (7 patients) and there was only 1 case of relevant restenosis on angiographic follow‐up. The overall incidence of major adverse cardiac events was 11 (4.9%). Conclusions: Mid‐term follow‐up after implantation of BVS suggests a satisfactory safety profile and low restenosis rate in routine daily practice involving a large range of complex lesions.